(untitled) (Contemporary Central & East European Law, 2024)
The interwar period marked the golden age of Polish administrative law, during which many of its key institutions were established or developed. One such institution was the model of public service, which – rooted in public law principles – comprehensively and logically shaped administrative law. Among the foremost figures shaping administrative law during that time was Professor Stanisław Kasznica. This article juxtaposes his thoughts and proposals with the current state of this field of Polish law, providing an assessment of the present condition of Polish administrative law.